2018
DOI: 10.5006/2786
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Corrosion Fatigue Life of Stainless Steel Joints Welded by Laser-Metal Active Gas Hybrid Welding

Abstract: The mechanical properties and corrosion resistance of the stainless steel (SS) corbel decline sharply after the welding process, which may cause serious accidents. Combining with microcharacteristics, mechanical properties, and corrosion properties, mathematic theories were used and an accurate prediction model of the corrosion fatigue life of SS butt joints produced by laser-metal active gas hybrid welding (LMHW) was established. The joints produced by LMHW have good mechanical properties, with the joint stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, when it comes to the advantages of laser and electron beam welding, such as penetration depth and high welding speed, lower specific heat input and thermal distortion, narrow weld and HAZs, high precision, ease of automation, etc. [3,15], then in the case of ASS or DSS welding, this is a controversial issue, since in this case high cooling rates lead to a negative effect on the phase balance of the weld metal and HAZ, and, accordingly, on the mechanical and corrosion properties [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when it comes to the advantages of laser and electron beam welding, such as penetration depth and high welding speed, lower specific heat input and thermal distortion, narrow weld and HAZs, high precision, ease of automation, etc. [3,15], then in the case of ASS or DSS welding, this is a controversial issue, since in this case high cooling rates lead to a negative effect on the phase balance of the weld metal and HAZ, and, accordingly, on the mechanical and corrosion properties [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the behavior of hydrogen in gray cast iron was similar to that of steel. With the increase of diffusive hydrogen content, critical stress would gradually decrease and the tendency to crack would gradually increase (Yang et al, 2018). Zhang et al studied the relationship between hydrogen and steel tensile strength and concluded that after hydrogen charging, the notch tensile strength of high-strength steel decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the action of corrosion, the fatigue strength of the welded steel components significantly decreased even after a short exposure time (approximately 10 days). Scanning electron microscopy (SEM) can be used to analyze the corrosion fatigue failure mechanism of welded metallic materials 14–18 . According to fracture analyses, pitting corrosion occurs on the surface of welded metallic materials during corrosion fatigue, which is one of the reasons leading to the nucleation of fatigue cracks 19,20 .…”
Section: Introductionmentioning
confidence: 99%